Edukasi Program Gerakan 1000 Hari Pertama Kehidupan (HPK) dalam Pencegahan Stunting dengan Media Promosi - Syarifah A'ini; Sopiah Widia Rahma Nst; Arifin Shaleh Lubis; Fakhreni Fakhreni; Reni Agustina Harahap (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The problem of nutrition which is currently the main focus and challenge for the Indonesian people is stunting.Stunting is a condition of malnutrition in toddlers which can cause growth failure so that the toddler does not grow and develop with its portion and low cognitive abilities. In general, the cause of stunting is usually due to lack of child nutrition for a long time, inadequate parenting from the time in the womb until the first 100 days of birth. Indonesia ranks fifth with a 36.4% percentage of stunting after India, China, Nigeria and Pakistan. With government policies, it has an influence on reducing stunting rates. However, the reduction in stunting rates in Indonesia is still far from the target. In 2012, the Indonesian government joined a nutrition improvement movement called the First 1000 Days of Life (HPK) Movement. The main focus of the movement is the first 1000 days of life for toddlers with the aim of improving the lives of Indonesian children in the future.Health promotion is closely related to the media because by using the media we can provide more interesting and easily understood information. The use of media can be in the form of audiovisual and non-audiovisual media. The use of this media is also seen from being received or captured by someone through the five senses. This research was conducted using the literature review method. Articles that are used as benchmarks are articles that are relevant within the last 3 years, using Indonesian or English, original research articles, and are available as free full text that can be accessed from Google Schoolar by using the keyword program 1000 Days of First Life (HPK), promotion media.